Evaluation of body condition score and early life events as risk factors for lameness in dairy cattle - Randall, Laura Vee (2018)
Lameness is one of the most significant challenges faced by the dairy industry worldwide. The negative impacts on the health, welfare and productivity of dairy cows means that controlling lameness is important for future sustainability. The aims of this thesis were to evaluate the risk factors for lameness in dairy cows, in particular body condition score (BCS) and early life events. Claw horn disruption lesions (CHDLs) are one of the major causes of lameness in dairy cattle, however their aetiopathogenesis is still poorly understood. The primary hypotheses explored within this thesis were related to risk factors for CHDLs in particular, with the aim of progressing the current knowledge and understanding of these lesions. Data obtained over an 8 year period (2003 to 2011) from the Crichton Royal research herd held at the Scotland’s Rural College (SRUC) Dairy Research and Innovation Centre in Dumfries, Scotland were used to investigate risk factors for lameness in dairy cows. The associations between fine thresholds of body condition score (independent of body weight) and lameness were explored using mixed effects multinomial and binomial logistic regression models. Cows with BCS < 2 in the previous 3-weeks were at greatest risk of mild or severe lameness. Low BCS was found to be associated with an increased risk of repeated lifetime lameness events in all animals, as well as first lifetime lameness events in cows in their second lactation or greater, indicating that low BCS may be an important risk factor for lameness in herds managed under similar conditions to the study herd. Furthermore, a novel approach to estimating population attributable fractions (PAF) for lameness risk factors which used simulation to investigate complex changes in herd BCS and previous lameness events over time in two dairy herds, showed that a loss in BCS of 0.5 across the whole herd may contribute towards between 4 and 11% of the total number of lameness events in these herds. Despite differences in methods of lameness identification (weekly locomotion scores versus treatment of clinical cases) and the environment between the herds investigated, the estimated PAF were similar, giving some indication that findings may be to some extent generalisable. In comparison to BCS, previous lameness events appeared to have a potentially larger impact on the total number of lameness events in the herd. The median estimated PAF for all previous lameness was between 79 and 83% in the two herds i.e. approximately 80% of lameness events in these two herds may be avoidable by preventing all previous lameness events. Between 9 and 21% of total lameness events may be attributable to previous lameness events occurring > 16 weeks before a risk period. These findings indicate that repeated lameness events (i.e. accumulation of lameness) may contribute towards a large proportion of herd level lameness. Preventing or increasing the time to first lameness events in a dairy herd may be important to reduce the number of repeat cases and lessen overall burden of lameness. Interactions with environmental and/or animal-based risk factors may also be important for preventing repeat lameness events. Further research is required to identify the reasons for and methods of preventing repeated lameness events, which could have considerable impact on reducing lameness at the herd level. The development of a method for estimating PAF for lameness risk factors using simulation enabled longitudinal data to be analysed, taking into account repeated measures and changes in risk factors over time. This is an important step forward in evaluating risk factors for lameness in dairy cattle, by identifying those that will have greatest impact on controlling disease in the population. Further work is needed to estimate the PAF for other risk factors including environmental factors. The large effect of previous lameness events on future lameness highlights the potential importance of lameness in heifers, as the future of the dairy herd. Mixed effects logistic regression models and linear regression were used to investigate the impact of hoof lesions in heifers around the time of first calving on milk yield, future lameness and culling risk. Severe claw horn disruption lesions (CHDL) post-calving were associated with an increased risk of future lameness and reduced milk yield (average daily and adjusted for the duration of time that cows spent within the herd), indicating that managing heifers to reduce severe CHDL could have positive benefits on health, welfare and production for the dairy herd. Mild CHDL pre-calving and 2 to 4 months post-calving were found to be associated with a decreased risk of future lameness and decreased culling risk. This novel finding suggests that some degree of mild insult may confer some resilience, if occurring at a time when heifers are able to cope, potentially through adaptive changes in the hoof. This suggests that management of heifers could have major impacts on lifetime claw health. The impact of previous lameness on herd level lameness was also investigated through exploring how different culling rates effect lameness prevalence, with the use of simulation. As herds with a lower culling rate will have an older age profile this increases the duration of time over which repeat lameness events might occur. Herds adopting a culling rate of 40% versus 20% were found to have a relative reduction in lameness prevalence of 29.2% (38.2% versus 27.1%, respectively). In herds with lower culling rates particular attention to lameness prevention and control may be necessary to maintain the health, welfare and productivity of the herd; this would be especially true for herds with a high background risk of lameness in month 1 of each lactation. Multilevel statistical modelling and simulation-based methods, combined with a rich longitudinal dataset, have aided in the identification of important key findings that contribute towards advancing our knowledge and understanding surrounding the aetiopathogenesis of lameness, and in particular CHDL. Identifying risk factors that, if controlled, will have the greatest effect on reducing lameness at the herd level is important and this work highlights where future research can build on this so that progress can be made in controlling lameness. This is relevant and important for the dairy industry worldwide.